Cause and effect analysis membership discontinuation: a case study - Hossain, Altaf (BRAC Research and Evaluation Division (RED), 2020)
Research and evaluation division of BRAC initiated the case study to look into the dropout matter for in-depth understanding of the causes and effect and policy implication of the issue. Two BDP area offices, one from low and one from high NGO concentrated area, were selected. Six VOs were selected including 3 from each area. Twelve dropout members from selected 6 YOs were taken for the case studies. Selected PRA techniques' such as, group discussion, physical mapping, in-depth interview, and wealth ranking exercises were used to collect information from dropout members, YO members, area office staff, and other community people. A questionnaire survey was also done on l 08 dropout members on some selected indicators. The study shows that the multidimensional reasons interplay, aggravate and give grounds for dropout. Inflexible savings and credit management policy, and various deductions are found to be the most common internecine causes of member's discontentment and dropout. In spite of long time membership, some members remain vulnerable to big economic and health related crisis and a little shock plunge them into dropout. Some members are also dropping out to join other NGOs to minimize opportunity cost in terms of distance, deductions etc. Well being status of some dropout members was at risk as their nutrition intake decreased, household assets diminished compared to when they were BRAC members and, in some cases, social support also decreased. Comparatively poorer members were exposed to vulnerability. While, some other dropout members who joined other NGOs experienced continuous economic improvement started during BRAC membership.